2020
DOI: 10.15251/cl.2020.179.457
|View full text |Cite
|
Sign up to set email alerts
|

HETEROJUNCTION p-Cu2SnS3/n-ZnO

Abstract: Conditions for the formation of a Cu2SnS3 film uniform in phase composition upon annealing of a metal layer of copper and tin in sulfur vapor in a quasi-closed volume chamber using the methods of X-ray spectral microanalysis and X-ray phase analysis are presented. The rectifying heterojunction p-Cu2SnS3/n-ZnO was fabricated. PACS numbers: 81.20.−n, 61.10.Nz, 84.60.Jt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…It has been theoretically shown that a single-junction solar cells (SCs) based on Cu 2 SnS 3 can have an efficiency of more than 30% [7]. Therefore, Cu 2 SnS 3 thin films have been extensively synthesized using various methods, such as magnetron sputtering [8], thermal evaporation [9], electro-deposition [10], sol-gel method [11], chemical bath deposition [12,13] and others [2,3]. To the best of our knowledge the highest efficiency values of SCs based on CTS have been achieved using vacuum methods [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been theoretically shown that a single-junction solar cells (SCs) based on Cu 2 SnS 3 can have an efficiency of more than 30% [7]. Therefore, Cu 2 SnS 3 thin films have been extensively synthesized using various methods, such as magnetron sputtering [8], thermal evaporation [9], electro-deposition [10], sol-gel method [11], chemical bath deposition [12,13] and others [2,3]. To the best of our knowledge the highest efficiency values of SCs based on CTS have been achieved using vacuum methods [2,3].…”
Section: Introductionmentioning
confidence: 99%